Backbone phylogeny and adaptive evolution of Pleurospermum s. l.: New insights from phylogenomic analyses of complete plastome data - Peng, Chang; Guo, Xian-Lin; Zhou, Song-Dong; He, Xing-Jin (Frontiers in Plant Science, 2023)
Pleurospermum is a taxonomically challenging taxon of Apiaceae, as its circumscription and composition remain controversial for morphological similarities with several related genera, leading to a dispute between Pleurospermum in the broad sense and strict sense. While evidence from previous molecular studies recognized plural branching lineages within the Pleurospermum s. l., it did not support the latest delimitation of Pleurospermum s. str. by only two closely related northern species. So far, no proper delimitation for Pleurospermum has come up, and many of the plural taxa in Pleurospermum s. l. remain unresolved, which may be due to poor phylogenetic resolution yielded barely from ITS sequences. Herein, we newly assembled 40 complete plastomes from 36 species of Pleurospermum s. l. and related genera, 34 of which were first reported and generated a well-resolved backbone phylogeny in a framework of the subfamily Apioideae. From the phylogeny with greatly improved resolution, a total of six well-supported monophyletic lineages within Pleurospermum s. l. were recognized falling in different major clades of Apioideae. Combining morphological characteristics with phylogenetic inference, we suggested to re-delimit the Pleurospermum s. str. by introducing nine species mainly from the Himalayan regions and proposed its boundary features; the remaining species were suggested to be excluded from Pleurospermum to incorporate into their more related taxa being revealed. On this basis, the plastome comparison revealed not only the high conservatism but also the mild differences among lineages in plastome structure and gene evolution. Overall, our study provided a backbone phylogeny essential for further studies of the taxonomically difficult taxa within Pleurospermum s. l.